Herpes zoster vaccination. An update - Khairuddin Djawad; Safruddin Amin; Anni Adriani; Widyawati Djamaluddin; Dirmawati Kadir; Sri Muchtar (Termedia Publishing House, 2022)
Herpes zoster/shingles is a cutaneous condition caused by the reactivation of varicella zoster virus. The condition mostly occurs when the cell mediated immunity towards varicella zoster virus, which was developed during the varicella zoster virus primary infection that causes varicella, decreases with increased age. The disease can cause various complications, most notably post herpetic neuralgia, which cause both significant health and socioeconomic burden, as well as impact the patient's quality of life. One of the steps we can take in combating this matter is vaccination. This article seeks to review the current options of herpes zoster vaccination and its efficacy, from the long-established live attenuated zoster vaccine and the recombinant adjuvant subunit vaccine.